Finding normal [videorecording (DVD)] - Irvingsen, Mark; Cameron-Bure, Candace, 1976-; St. John, Trevor; Beatty, Lou, Jr; Bongiorno, Andrew (Pure Flix Entertainment, 2014)
The only thing standing between Dr. Lisa Leland and the wedding of her dreams in the Hamptons is a 2,600-mile drive from Los Angeles to her new life. However, a run-in with the law in the country town of Normal, NC, leaves Dr. Leland with a choice: jail or community service. Sentenced to serve three days as the town's doctor, Lisa has her world turned upside down by a man she would never expect. Quickly, Lisa finds that there's a lot more to Normal than she could have ever imagined.